2008
DOI: 10.1038/bjp.2008.286
|View full text |Cite
|
Sign up to set email alerts
|

Dietary trace amine‐dependent vasoconstriction in porcine coronary artery

Abstract: Background and purpose: The dietary trace amines tyramine and b-phenylethylamine (b-PEA) can increase blood pressure. However, the mechanisms involved in the vascular effect of trace amines have not been fully established. The purpose of this study was to evaluate whether trace amine-dependent vasoconstriction was brought about by tyramine and b-PEA acting as indirect sympathomimetic agents, as previously assumed, or whether trace amine-dependent vasoconstriction could be mediated by recently discovered trace … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 40 publications
2
24
0
Order By: Relevance
“…Explanation for such SMA BFV increase in the probiotic group could be potentially found in animal studies, 7,8 which investigated the role of probiotic-generated trace amines (tyramine and b-phenylethylamine). In guinea-pig and rat models, mesenteric vasculature, rings of aorta and coronary arteries were isolated and exposed to the gradually increasing concentrations of tyramine and b-phenylethylamine, leading to vasoconstriction of the aorta and coronary arteries and relaxation of the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanation for such SMA BFV increase in the probiotic group could be potentially found in animal studies, 7,8 which investigated the role of probiotic-generated trace amines (tyramine and b-phenylethylamine). In guinea-pig and rat models, mesenteric vasculature, rings of aorta and coronary arteries were isolated and exposed to the gradually increasing concentrations of tyramine and b-phenylethylamine, leading to vasoconstriction of the aorta and coronary arteries and relaxation of the mesenteric vascular bed.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, it has been reported that probiotics are a source of the trace amines, tyramine and b-phenylethylamine, which affect vasculature independently via recently described trace amineassociated receptors. 7,8 In animal models, amines exert differential effects on aorta/coronary arteries and mesenteric vasculature, causing relaxation of mesenteric vasculature and subsequent improvement in the intestinal blood flow. It has been well established that alterations in intestinal blood flow have an impact on tolerance to enteral feedings in preterm neonates.…”
Section: Introductionmentioning
confidence: 99%
“…Our results indicate that RAC, contrary to expectations, is not an agonist of the hb 2 AR but rather is a full agonist of the closely related mTAAR1. Since TAAR1-mediated signaling can influence cardiovascular tone (Fellows, 1947;Frascarelli et al, 2008;Herbert et al, 2008;Broadley, 2010;Fehler et al, 2010;Broadley et al, 2013) and behavior in several animal models (Miller, 2011;Revel et al, 2011;Achat-Mendes et al, 2012), our finding that RAC is a full mTAAR1 agonist constitutes a novel mechanism by which RAC can influence the physiology and behavior of pigs (Marchant-Forde et al, 2003;Poletto et al, 2009Poletto et al, , 2010a and other species. These findings should stimulate future studies to characterize the pharmacological, physiological, and behavioral actions of RAC in humans and other species exposed to this drug.…”
Section: Introductionmentioning
confidence: 86%
“…The pressor response that was induced by the trace amine tryptamine in mesenteric vessels was abolished by ketanserin and ritanserin, two 5‐hydroxytryptamine (5‐HT) receptor antagonists . In contrast, β‐PEA‐induced vasoconstriction in porcine coronary artery was unaffected by the 5‐HT receptor antagonist ketanserin …”
Section: Introductionmentioning
confidence: 99%